Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-020-15335-4
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic fish predation is stronger at temperate latitudes than near the equator

Abstract: Species interactions are widely thought to be strongest in the tropics, potentially contributing to the greater number of species at lower latitudes. Yet, empirical tests of this "biotic interactions" hypothesis remain limited and often provide mixed results. Here, we analyze 55 years of catch per unit effort data from pelagic longline fisheries to estimate the strength of predation exerted by large predatory fish in the world's oceans. We test two central tenets of the biotic interactions hypothesis: that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Except the LDGs, study on pelagic fish predation also found a bimodal gradients that stronger predation was higher at temperate than equatorial area (Roesti et al, 2020). Therefore, latitudinal gradients on other topics, such as phylogenetic, physiological, functional traits or ecological interaction of fish are worth for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Except the LDGs, study on pelagic fish predation also found a bimodal gradients that stronger predation was higher at temperate than equatorial area (Roesti et al, 2020). Therefore, latitudinal gradients on other topics, such as phylogenetic, physiological, functional traits or ecological interaction of fish are worth for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, the LBIH was tested at different scales—from global patterns across biomes to within‐biome gradients. These studies provided mixed support for the LBIH (Adams & Zhang, 2009; Baskett & Schemske, 2018; Kozlov, Lanta, et al., 2015; Moles, Bonser, et al., 2011; Roesti et al., 2020; Roslin et al., 2017), and the variability of outcomes between case studies inspired the search for the sources of controversy surrounding latitudinal patterns in biotic interactions (Anstett et al., 2016). One of these sources may be the variation between different types of interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this conception, diversity begets diversity in a positive feedback loop. Whether species interactions are stronger in the tropics has been tested by many studies, with mixed results (Schemske et al 2009;Anstett et al 2016;Moles & Ollerton 2016;Roslin et al 2017;Baskett & Schemske 2018;Hargreaves et al 2019;Freeman et al 2020;Roesti et al 2020). However, the prediction that stronger species interactions or higher diversity can drive faster evolution in the tropics remains largely unexplored (but see Benkman 2013).…”
Section: Introductionmentioning
confidence: 99%